Femme fatale: a natureza insólita da mulher fatal na literatura brasileira - FERREIRA, Bruna Letícia Menezes (2024)
This research explores the figure of the femme fatale in speculative literature, analyzing her evolution and presence in narratives that challenge reality, with a particular focus on Brazilian literature. Divided into three chapters, the study employs a bibliographic and exploratory methodology, drawing on theorists such as Mario Praz (1961), Jennifer Hedgecock (2008), Heather Braun (2012), and Camille Paglia (1992) to investigate the mythic and literary origins of the femme fatale, tracing her transformation to modern times. The first chapter examines the rise of the femme fatale in world literature, from divine and mythological figures to complex characters in 20th-century literature, reflecting on nuances of power, seduction, and transgression. The second chapter delves into speculative literature and the impact of the femme fatale in genres such as science fiction, fantasy, and horror, highlighting the potential of these imaginative realms to question and reimagine gender roles and morality. Theorists like Charles Nodier (1970), Tzvetan Todorov (1980), H. P. Lovecraft (1969), and Pierre George Castex (1962) provide a solid foundation for analyzing the femme fatale in speculative fiction through themes of fear, hesitation, and solitude. The final chapter focuses on central female characters in Brazilian literature: Augusta, Alzira, and Céluta, respectively protagonists of “O Capitão Mendonça” (1870) by Machado de Assis, A Mortalha de Alzira (1895) by Aluísio Azevedo, and “A Sombra” (1927) by Coelho Neto. The analysis reveals how these authors integrated the femme fatale figure, blending supernatural, scientific, and social aspects to reflect on female representation.